Beyond Discrete Categories: Studying Multiracial, Intersex, and Transgender Children Will Strengthen Basic Developmental Science. Issue 4 (7th August 2016) - Dunham, Yarrow; Olson, Kristina R.
Abstract : Developmental research on social categorization has overwhelmingly focused on perceptions about and experiences of individuals who are clear or prototypical members of discrete and usually dichotomous social categories. For example, studies of social categorization, stereotyping, prejudice, and social identity have generally explored how children reason about others who are gender-typical boys or girls or monoracial White or Black children. Similarly, research participants have generally been gender-typical and monoracial. However, our efforts to build theories that account for the true range of variation require acknowledging the increasing visibility of children who do not fit into these discrete categories and raise the question of whether existing theories can capture the dynamics that arise for them. Focusing on race and gender/sex, the social categories that have received the most attention in the developmental literature, we review research that has gone beyond simple dichotomies by including multiracial, gender-nonconforming, or intersex children, either as the targets of social perception or as participants themselves. We argue that this emerging work reveals problematic assumptions built into our theories and methods and highlights the value of building a more inclusive science.